Comparative study of two different zeolites BEA and ZSM-5 exchanged by copper and iron via the oxidation of phenol by hydrogen peroxide - TALHAOUI, Fatiha; HAMIDI, Fatiha; Medina, Fransisco (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/Purpose: Water pollution by organic compounds such as phenol poses a major environmental risk. This study aims to compare the catalytic efficiency of ZSM-5 and BEA zeolites, doped with iron (Fe) and copper (Cu), for the wet oxidation of phenol using hydrogen peroxide (H₂O₂).Method: BEA and ZSM-5 zeolites were synthesized via hydrothermal methods, then ion-exchanged to incorporate Cu²⁺ and Fe²⁺. The catalysts were characterized using XRD, FTIR, SEM, and XPS. Phenol oxidation was carried out at 80 °C in aqueous medium with an H₂O₂/phenol molar ratio ranging from 10:1 to 15:1. The reaction products were analyzed by HPLC.Results: The crystalline structures of the zeolites were maintained after ion exchange. The metals were well dispersed on the surface. Fe-BEA and Fe-ZSM-5 catalysts showed the highest activity (up to 99% conversion), followed by Cu-BEA (88%) and Cu-ZSM-5 (68%). The pure zeolites exhibited low activity (
Keywords: ZSM-5; BEA; Hydrogene peroxide; Phenol oxydation; heterogeneous catalysis